2016
DOI: 10.1186/s13104-016-1995-5
|View full text |Cite
|
Sign up to set email alerts
|

Gastric fundal heterotopic pancreas mimicking a gastrointestinal stromal tumour (GIST): a case report and a brief review

Abstract: BackgroundHeterotopic pancreas is a rare congenital condition characterised by pancreatic tissue lacking vascular or anatomic communication with the normal pancreas. Most cases of ectopic pancreas are asymptomatic. The preoperative diagnosis of this condition is difficult.Case presentationA 50-year-old woman presented with dyspeptic symptoms of 4 years duration. Contrast enhanced CT (computed tomography) scan of abdomen suggested a gastrointestinal stromal tumour in the fundus of the stomach. The patient under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
(19 reference statements)
2
15
0
Order By: Relevance
“…Although gastroscopic biopsy is regarded as the gold standard for the diagnosis of tumors, limitations include its invasive nature, sampling errors, diagnostic errors, long waiting times for immunohistochemistry results [ 9 ], and powerless assessing situations outside the tumor. Computed tomography (CT), as a common imaging examination method, has been used in the preoperative evaluation of submucosal tumors, and can be used as a supplemental tool in differentiating HP masses from STs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gastroscopic biopsy is regarded as the gold standard for the diagnosis of tumors, limitations include its invasive nature, sampling errors, diagnostic errors, long waiting times for immunohistochemistry results [ 9 ], and powerless assessing situations outside the tumor. Computed tomography (CT), as a common imaging examination method, has been used in the preoperative evaluation of submucosal tumors, and can be used as a supplemental tool in differentiating HP masses from STs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been conducted on the imaging features of HP masses and gastric stromal tumors (STs), most have employed endoscopic ultrasonography [ 11 , 12 ], with few adopting CT characteristics, and most have been case reports [ 10 , 13 ]. To our knowledge, no studies have reported CT findings for differentiating gastric submucosal tumors less than 3 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence range is reported to be between 0.5% and 13.7% of autopsies [2]. The most common location along the gastrointestinal tract (GIT) is the stomach (38%) and the small bowel [9]. If symptomatic, patients present with pancreatitis, pain, bleeding, obstruction, or malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although heterotopic pancreas can present at any age, it is usually discovered in the fifth and sixth decade, and is three times more likely to occur in men than women (4). When gastric, the heterotopic tissue is located in over 50% of the cases within 5 cm of the pylorus.…”
Section: Discussionmentioning
confidence: 99%